Effects of freezing on ability to detect Mycobacterium avium subsp. paratuberculosis from bovine tissues following culture - Corbett, Caroline S. (J Vet Diagn Invest, 2018)
Mycobacterium avium subsp. paratuberculosis (MAP) is the bacterium that causes Johne’s disease in cattle. Although infected cattle can be identified by examining fecal, blood, or milk samples, the gold standard is identification of MAP in tissue samples postmortem. Although tissue samples are commonly frozen, the ability to detect MAP in frozen–thawed tissue samples has apparently not been reported. We therefore determined the ability to detect MAP in tissue samples following freezing. Tissue samples were collected from calves that were either inoculated (IN) 3 mo prior, or contact-exposed (CE) for 3 mo. Following autopsy, tissues were immediately processed for culture, followed by DNA extraction and detection by qPCR. Samples were categorized as positive or negative based on the cycle threshold (Ct) value. The remaining unprocessed tissue samples were frozen at −80°C. After 18 mo, 50 tissue samples designated MAP-positive were thawed and processed for detection of MAP. Four (8%) samples were qPCR-negative, and Ct values of the remaining 46 samples were higher after freezing. Given the small numerical change in Ct values for MAP-positive samples after 18 mo of frozen storage, freezing and thawing may have had some deleterious effects on MAP detection in tissues. Although the decrease in ability to detect MAP-positive samples was minor for IN calves, there may be a greater effect for CE calves that should be considered when freezing tissue samples.